The Relationship Between USD/EUR Official Exchange Rates And Implied Exchange Rates From The Bitcoin Market - Sebastião, Helder (2020)
We examine the long- and short-run relationships between USD/EUR official rates and implicit exchange rates, through Bitcoin as a currency vehicle, over the period from March 07, 2016 to November 22, 2019. The results show that the two exchange rates are cointegrated and that the cointegrating vector is not statistically different from the theoretical one that results from the law of one price. In the short-run, the implied rate Granger-causes the official reference rate. Our main conclusion is that Bitcoin USD and EUR prices incorporate fundamental information from the USD/EUR official exchange rate